The effect of the Fitostemin-WP® biostimulator on yield and quality characteristics of rice (Oryza sativa L.) - Spaseva Brankica; Mitrushev Ivo; Andreevska Danica; Andov Dobre (Agroznanje, 2024)
In order to avoid yield and quality reduction of rice, it is essential to provide nutrition rice plants require. Therefore, a field experiment was conducted at the research area of the Institute of Agriculture - Skopje, Department of Field Crops, Ss. Cyril and Methodius University in Skopje, Republic of Macedonia, in Kochani, a rice production region. The experiment was set up to determine the effects of the Fitostemin-WP® biostimulator on some yield and quality properties of an Italian rice variety Opale during the vegetative seasons in 2020 and 2021. Standard agrotechnical methods for crop production were applied. Fitostemin-WP® is an herbal product in the form of powder and it consists of herbal extracts and minerals. It is used for increasing crop yield. The field experiment was arranged in a Zade method with a Fitostemin-WP® treatment and a control one in 3 replications. Only basic fertilizers (350kg/ha NPK and 200kg/ha Urea (46% N)) were applied on the control plot, while the treatment plot, besides basic fertilization, was also treated with Fitostemin-WP® with 100 g/ha dosage once during the vegetation period (tillering stage). The following parameters were examined in this study, namely the biological, grain and straw yield, the number of productive tillers/m2, panicle weight, and milling fractions. Results were analyzed with the ANOVA and LSD test. According to the results from this study, statistically significant differences were not found in these two years of field experiments for the examined parameters. However, the values for the brokens have shown some significant differences between the years, but not between the treatment and the control. This can result from the environmental impact during the vegetative period. More frequent usage of Fitostemin-WP® during the vegetation period of the rice plant may show more significant results.